Model Kelas Industri pada Mitsubishi School Program di Sekolah Menengah Kejuruan - Hamzah Achsani; Djoko Kustono; Syarif Suhartadi (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The focus of learning in Vocational High Schools needs to be emphasized on the mastery of skills, knowledge, attitudes and values needed by industry. This study aims to describe the industrial class model in the Mitsubishi School Program that has been carried out in Vocational High School. The research method this is a qualitative approach with type of descriptive research, object of research is Private Vocational High School Muhammadiyah 6 Rogojampi on MSP industrial grade automotive engineering expertise program. The results of this study are industrial class model begins planning by collaborating with the school and industry and continued with the collaboration of the preparation of the industrial class curriculum between the VHC curriculum and industrial qualifications. The implementation process is adjusted to the curriculum that has been prepared. The evaluation of the industrial class program is carried out after the process of implementing the industrial class by both parties.Abstrak: Fokus pembelajaran di SMK perlu menekankan penguasaan keterampilan, pengetahuan, sikap, dan nilai-nilai yang dibutuhkan industri. Tujuan dalam penelitian ini adalah mendeskripsikan model kelas industri pada Mitsubishi School Program yang telah dilakukan di SMK. Metode penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif, objek penelitiannya yaitu SMK Muhammadiyah 6 Rogojampi pada program keahlian teknik otomotif kelas industri Mitsubishi School Program. Hasil penelitian didapatkan model kelas industri diawali perencanaan dengan melakukan kerjasama antara pihak sekolah dengan industri dan dilanjutkan dengan kolaborasi penyusunan kurikulum kelas industri antara kurikulum SMK dan kualifikasi industri. Proses pelaksanaan disesuaikan dengan kurikulum yang telah disusun. Evaluasi program kelas industri dilaksanakan setelah proses pelaksanaan kelas industri oleh kedua belah pihak.